ABUNDANCE AND STRUCTURE OF SOIL INVERTENRATES (MACROFAUNA) OF THE VIRGIN STEPPE OF THE SOUTHERN CHERNOZEM ZONE (KOSTANAY REGION) - Bragina, T.M.; Guggenberger, G.; Bobrenko, M.A.; Doreen, F.; Rulyova, M.M.; Schibistova, O.B. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2022)
The soil fauna represents one major living constituent of soils, being important for the functioning of soils. The goal of our research was to analyze the abundance, structure and habitat of soil macrofauna communities on virgin soils of the southern chernozems zone of the Kostanay region. The soil is characterized by high contents of microbially transformed organic matter and of exchangeable cations. Soil invertebrate communities (macrofauna) were dominated by insects (89,0%), among which Coleoptera predominated (54,0%). The predominance of eurybiont species reflects the peculiarities of the climate and the diversity of vegetation.
Численность и структура почвенной макрофауны (беспозвоночных) целинной степи на южном черноземе Костанайской области
Keywords: macrofauna; Insects; Invertebrates; Kostanay region; virgin soil; Southern chernozems